Ischemia-modified albumin levels in children with asthma: A pilot study - Doğru, Mahmut; Akoğlu, Handan; Kılınçkaya, Muhammed Fevzi; Ülfer, Gözde (Sociedad Argentina de Pediatría, 2018)
Introduction: Hypoxia may occur in the severe exacerbations of asthma. Ischemia-modified albumin (IMA) may increase in ischemia, in addition to oxidative stress and inflammation. The aim was to evaluate IMA levels in children during the asthma exacerbation and the asymptomatic period. Populations and methods: Children with asthma who were followed up in our clinic were included and healthy children were selected as the control group. The severity of exacerbation was evaluated with Global initiative for Asthma and Modified Pulmonary Index Score. Serum IMA levels were measured at the time of exacerbation and 4 weeks after treatment during asymptomatic period. Skin prick test and C reactive protein (CRP) levels were measured. Results: A total of 26 patients and 26 controls were included. Mean IMA level was 0.45 +/- 0.12 absorbance units -ABSU- during asthma exacerbation and 0.32 +/- 0.08 ABSU in the control group (p=0.001). Mean IMA levels (0.41 +/- 0.14 ABSU) during the stable period were higher than the control group (p=0.005). There was no difference in terms of IMA levels when patients were grouped according to anti-inflammatory treatment, upper respiratory tract infection before exacerbation, CRP levels or sensitivity of skin prick tests. However, IMA levels were higher in patients with severe asthma exacerbation (p=0.009) in comparison with mild /moderate exacerbation. Positive correlation was observed between IMA levels and severity of exacerbation (r: 0.498, p=0.010). Conclusions: Asthmatic children had higher IMA levels than the control group, both in stable and exacerbated asthma. There was a positive relationship between IMA levels and severity of asthma exacerbation.
WOS: 000439814600012
PubMed ID: 30016026
Keywords: Asthma; Child; Asthma Exacerbation; Hypoxia; Ischemia-Modified Albumin